1967
DOI: 10.1139/p67-310
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Wave Propagation Over a Nonparallel Stratified Conducting Medium

Abstract: The objective is to calculate the electromagnetic field of a dipole located over a flat inhomogeneous ground whose upper layer has a variable thickness. Although a formally exact derivation for a lossy dielectric wedge model is available, its complexity prohibits immediate application. Instead, using a geometrical-optical technique, an approximate expression is developed for the effective surface impedance at the ground surface. This method takes full account of multiple reflections within the wedge region but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The solutions are shown to be consistent with the reciprocity relationship. Some of the terms of the full-wave solution can be predicted directly through a geometrical optical approach [Schlak and Wait, 1967]. However, the geometrical-optical approach is limited in its application, since it does not satisfy the reciprocity relationship and the excitation of the surface waves is not accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The solutions are shown to be consistent with the reciprocity relationship. Some of the terms of the full-wave solution can be predicted directly through a geometrical optical approach [Schlak and Wait, 1967]. However, the geometrical-optical approach is limited in its application, since it does not satisfy the reciprocity relationship and the excitation of the surface waves is not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy, which decreases with increasing distance between the two dipoles over dissipative overburdens, is attributed to the approximations inherent in the geometrical-optical approach. The experimental results obtained by Schlak and Wait [1967] were not considered sufficiently accurate to resolve this problem. Recently King and Hustig [1971 ], who conducted controlled model experiments using low-loss dielectrics, showed that the surface impedance (which does depend upon the direction of propagation) cannot, in general, be evaluated by the geometrical-optical approach.…”
Section: Derivation Of the Scattered Fields From The Wave Amplitudementioning
confidence: 99%
See 1 more Smart Citation
“…This is justified when all significant dimensions are small compared with the wavelength. Now if we apply a geometrical-optical argument, such as used by Schlak an Wait [ 1967], the field at P is the sum total of all the ray contributions between the cable and the observer. The first four of these are depicted in Figure 1.…”
Section: Wedge Modelmentioning
confidence: 99%
“…Notable work in this area is by Bahar [ 1970], who has treated such problems as coupled modes in a waveguide of variable cross section; by Geyer [1972], who has utilized Lebedev-Kontorovich transforms; and by Jones [1970] who solved the differential equations for a step-structure by a purely numerical method. Recently, Balling [ 1971 ] has suggested that the geometrical optical formulation of Schlak and Wait [ 1967] for wedge geometries be generalized to allow for the full spectrum of complex angles in the primary field. We wish to pursue this approach here from the standpoint of electromagnetic induction in a stratified conducting earth.…”
Section: Introductionmentioning
confidence: 99%